Biallelic Heterozygous Mutations in Crumbs Homolog-1 Gene Associated With Macular Retinoschisis and Angle-Closure Glaucoma: A Case Report and Literature Review - Sun, Jia-Xing; Yan, Hong-Xiang; Hu, Dan; Zhou, Jian; Wang, Yu-Sheng; Wu, Jing; Song, Xiao-Jin; Hou, Xu (Frontiers in Ophthalmology, 2022)
Background: Mutations in the Crumbs homolog-1 (CRB1) gene are associated with a variety of retinal degenerations including Leber congenital amaurosis (LCA) and retinitis pigmentosa (RP). It is also important to highlight atypical features to make proper diagnosis and treatment. Case presentation: We present the case of a 7-year-old girl with biallelic heterozygous CRB1 mutations. The clinical features include macular retinoschisis, Coats-like vasculopathy, short axial length, and angle-closure glaucoma (ACG). We also briefly review the current opinion of CRB1 mutation-related diseases. Conclusion: CRB1 mutations could result in a combined manifestation in anterior and posterior segments. This case emphasizes the importance of genetic diagnosis for those young patients with complicated rare clinical features to call for a specific treatment and follow-up plan. It also highlights the crucial role of CRB1 in eyeball development.